Religious Moderation In Economic Sharia For Developing Welfare's People - Mutmainah, Mutmainah; Mardi, Moh.; Farhami, Al Azaz (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2023)
Excessive fanatical diversity is one of the problems in Indonesia if adherents of a religion that has it gives rise to radicalism, which often carries out violent movements such as: hate speech, attacks, kidnappings, suicide bombings, and so on. Extremist ideology (ghuluw) is not in accordance with the concept of Islam, because it eliminates harmony in religious togetherness so that it is difficult to create prosperity for the people, therefore it is necessary to have programs and activities carried out in the context of implementing and strengthening religious moderation as formulated in the five priority activities (KP) One of the technocratic RPJMN 2020-2024 is the development of economic and religious resources.This research is research aimed at analyzing religious moderation in the development of sharia economics as an effort to improve community welfare. This research is library research (library research), Data analysis techniques using the Milles and Huberman model include: (1) data reduction, (2) data display, and (3) conclusion drawing. Results Research Based on the discussion, it can be concluded that: Sharia economics is an economy that supports truth and justice and rejects all forms of economic behavior that are not good and evil, such as: usury, speculation, fraud, and uncertainty or lack of clarity (gharar). This is in line with the attitude of religious moderation which is a religious perspective, attitude and practice which is the embodiment of the essence of Islamic teachings where sharia economics has the characteristics of-characteristics of moderate Islam that differentiate sharia economics from capitalist and socialist economies include: tawassuth (taking the middle path), tawazun (balanced), i'tidal (straight and firm), tasamuh (tolerance), musawah (egalitarian), shura (deliberation), ishlah (reform), aulawiyah (putting priorities first), and tatawwar wa ibtikar (dynamic and innovative), by prioritizing fair, balanced principles to uphold human dignity as a national agreement and comply with the constitution in order to achieve the benefit and welfare of the people.